Utilization of Swietenia mahagoni Seed Extract To Controling of Paracoccus marginatus on Nurseries of Acacia crassicarpa - Emanuel M. Y. Hanoe (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2022)
Resources management nature becoming point to important especially in maintaining benefits, continuity and sustainable natural source.Natural resource potential available with proper management would be of avail for human life.Natural resource potential can be attraction the community and can be used as tourist destinations. The area of tanjung bastian is one of the area who was in District North Central Timor are identical to the beach and also the racetrack and natural scenery. The effort to maintain the condition ecology in Tanjung Bastian related in such as planting tourism areas with the aim of land conservation as vegetation regeneration. A condition of vegetation survival in a stable and being able to compete with the physical condition of extreme environmental and climate condition, it is necessary to evaluate the extent to which the level of success of tree growth and the factors that influence it. Based on the results of observation plants who succeeded life 53 a plant consisting of 6 species with the numbers of life most there are to a species Delonix regia as many as 15 plants and the least species is Senna siamea with 3 plants. The classification of the assessment criteria vegetation that the level of success of success in the vetegasi Tanjung Bastian included in a category in quite poor repair the 57,3%.